2017
DOI: 10.1093/emph/eox011
|View full text |Cite|
|
Sign up to set email alerts
|

Local environmental quality positively predicts breastfeeding in the UK’s Millennium Cohort Study

Abstract: Using breastfeeding initiation and duration and local-level indicators of environmental quality, we test the life history theory prediction that parental investment will be lower in harsh environments. We find that local environmental quality (as rated by an independent assessor) positively predicts breastfeeding over and above the influences of individual SES and the wider environment. Higher SES also appears to buffer against the negative effects of lower local environmental quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 99 publications
3
7
0
Order By: Relevance
“…Taken together, these mediation results suggest that mothers with low birthweight and shorter gestation lengths have reduced breastfeeding chances, a finding corroborated by our previous analyses of the Millennium Cohort Study (Brown & Sear, ) that showed that lower birthweight infants had lower initiation rates and average breastfeeding durations (e.g., 67% and 2.07 months vs. 69% and 2.69 months for normal weight and 74% and 3.11 months for heavy weight). Low birthweight and preterm birth (i.e., when gestational lengths are shorter than 37 weeks) may negatively impact breastfeeding in several ways.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Taken together, these mediation results suggest that mothers with low birthweight and shorter gestation lengths have reduced breastfeeding chances, a finding corroborated by our previous analyses of the Millennium Cohort Study (Brown & Sear, ) that showed that lower birthweight infants had lower initiation rates and average breastfeeding durations (e.g., 67% and 2.07 months vs. 69% and 2.69 months for normal weight and 74% and 3.11 months for heavy weight). Low birthweight and preterm birth (i.e., when gestational lengths are shorter than 37 weeks) may negatively impact breastfeeding in several ways.…”
Section: Discussionsupporting
confidence: 85%
“…This could be because duration was measured on a smaller, less representative sample, with less power to detect effects. However, we also found stronger initiation than duration results in our previous study (Brown & Sear, ), suggesting that initiation may be genuinely more strongly influenced by environmental quality than duration. It is likely that breastfeeding duration is more influenced by other factors such as women needing to return to work (Andrew & Harvey, ; Heck, Braveman, Cubbin, Chávez, & Kiely, ; Huang & Yang, ; Kimbro, ; Rippeyoung & Noonan, ).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations